Analisis Potensi Media Promosi Instagram UC Library Melalui Komik Digital - Abhina Salma Yunita; Ade Ayu Syafira Nasution; Dyllan Johnathan; Patrick Almayda Sesar (Universitas Ciputra Surabaya, 2022)
The research on analyzing the potential of online promotion media of UC Library through digital comics is a scientific research for the Instagram social media of UC Library, which contains a lot of content. One of which is comic content. This research aims to see the effectiveness of using this comic compared to other content, and to compare before using comic as a content. This research adopts the literature research methodology through several journals as the source to help with the research. The results of this research could help evaluate the optimization of the UC Library's social media content in the future. Keywords: Social media, Comic, Marketing, UC Library